Patch BoneAux: uma ferramenta gratuita desenvolvida para auxiliar o aprendizado e aprimoramento do trombone de vara - Alves, Breno Novaes (2021)
The creation and use of technological tools to facilitate the musical development of professionals and apprentices has become increasingly frequent nowadays. However, most of these tools still do not meet the necessary pedagogical criteria desired in music-making. Indeed, there is a lack of its use in academia, and professionals to encourage its use. This work proposed the creation of a prototype of a digital play-along program based on Design Science Research and the Subsumption Theory, capable of assisting in technical-musical development, both in the study environment and in performance practicing. This tool also sought to encourage the immersion of musicians in handling these technologies. In this way, they could either develop or collaborate on creating this equipment. One of the premises of this work was that the entire development process used open-source software to encourage low-budget learning. Thus, it will be usable in public schools, community bands. This artifact is called Patch BoneAux. Its structure contains layers of functions and subfunctions. All of them are interconnected by Object-Oriented developed from the free software Pure Data (Pd) with connections via QjackCtl, Patchage, and Qsynth, and Soundfonts triggered by MIDI instructions for playback and musical accompaniment. Our goal was to provide a play along containing more flexible tempi to meet the different levels of complexity of the songs. In this way, instrumentalists can perform on rests, playback, and recording. The author also used a systematic survey, The DSR, and the Subsumption Theories as the theoretical basis to conclude his biographical review. Based on the obtained literature, requirements were elaborated within problem classes seeking rigor and relevance for creating this artifact. A Workshop was held by 16 professional trombonists (artists and pedagogues), within members of the project of extension of the Federal University of Paraíba (UFPB), entitled "Trombones in Quarantine" to validate the software. The interaction on the part of the professionals who visualized the tool's functionalities. This technical recognition allowed us to understand the usefulness of the artifact for technical-musical development from beginners to music professionals.